2013
DOI: 10.1136/annrheumdis-2012-202794
|View full text |Cite
|
Sign up to set email alerts
|

A phase 1b clinical trial evaluating sifalimumab, an anti-IFN-α monoclonal antibody, shows target neutralisation of a type I IFN signature in blood of dermatomyositis and polymyositis patients

Abstract: ObjectiveTo assess the pharmacodynamic effects of sifalimumab, an investigational anti-IFN-α monoclonal antibody, in the blood and muscle of adult dermatomyositis and polymyositis patients by measuring neutralisation of a type I IFN gene signature (IFNGS) following drug exposure.MethodsA phase 1b randomised, double-blinded, placebo controlled, dose-escalation, multicentre clinical trial was conducted to evaluate sifalimumab in dermatomyositis or polymyositis patients. Blood and muscle biopsies were procured be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
93
0
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(99 citation statements)
references
References 30 publications
1
93
0
5
Order By: Relevance
“…Current medical efforts are focused on the development of antibody-based drugs (sifalimumab, rontalizumab, etc.) for neutralizing IFNAR1 in patients with diverse inflammatory/ autoimmune syndromes (61,62). Our data suggest that a similar strategy could be potentially envisioned for relieving IFN-mediated pancreatotoxicity in patients with Wolcott-Rallison or patients who receive PERK inhibitors for treating tumors (22)(23)(24) and prion-mediated neurogenerative disorders (25).…”
Section: Discussionmentioning
confidence: 83%
“…Current medical efforts are focused on the development of antibody-based drugs (sifalimumab, rontalizumab, etc.) for neutralizing IFNAR1 in patients with diverse inflammatory/ autoimmune syndromes (61,62). Our data suggest that a similar strategy could be potentially envisioned for relieving IFN-mediated pancreatotoxicity in patients with Wolcott-Rallison or patients who receive PERK inhibitors for treating tumors (22)(23)(24) and prion-mediated neurogenerative disorders (25).…”
Section: Discussionmentioning
confidence: 83%
“…Gevokizumab, a potent monoclonal antibody binding strongly to IL-1 beta, is currently being studied in a global clinical trial [89]. In a first phase 1b clinical trial [91], sifalimumab showed a moderate suppression of cluster of genes induced by type I IFN, highly over-expressed in IIM patients compared to controls. Positive correlation between gene neutralization and improvement of muscle strength by MMT8 was also recorded.…”
Section: Anakinramentioning
confidence: 99%
“…Therefore, MEDI-545 (Sifalimumab), an anti-IFN-α monoclonal antibody, was trialed in refractory PM/DM (NCT00533091). This phase 1B study found suppression of IFN in blood and muscle and some clinical improvement, suggesting that further studies may be worthwhile [106].…”
Section: Cytokine-based Therapiesmentioning
confidence: 61%